Implementasi Pembelajaran Deep Learning dalam Manajemen TK Berbasis PAUD Holistik Integratif - Sabrina Wahyuningtyas Ananda Putri; Najma Aulia; Rubiatul Adawiah; Novi Aulia; Hasbi Sjamsir; Fachrul Rozie (BEduManagers Journal : Borneo Educational Management and Research Journal, 2026)
Abstract This study aims to analyze the implementation of deep learning in kindergarten management based on Holistic Integrative Early Childhood Education. This research uses a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The results show that deep learning has been implemented through child-centered activities such as play, exploration, and direct experience. However, its implementation has not been fully integrated systematically into lesson planning. Kindergarten management plays an important role in integrating deep learning with the holistic integrative approach, which includes education, health, and child welfare aspects. In addition, stakeholder involvement and continuous evaluation support the success of implementation. Therefore, strengthening management aspects and teacher competence is needed to optimize learning and support children's holistic development.